The interpretation of business interruption clauses in South Africa : a constitutional analysis - Ncube, Princess Thembelihle (University of Pretoria, 2025)
Mini Dissertation (LLM Mercantile Law : Insurance Law and Governance))--University of Pretoria, 2023.